PENERAPAN PENDEKATAN PEMBELAJARAN BRIDGING ANALOGY UNTUK MENINGKATKAN KEMAMPUAN METAKOGNITIF SISWA - EFRIANA JON (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Based on the observations and interviews that the authors carried out in SMA Negeri 3 Kerinci obtained information on the average value of the semester odd semester of class X students is still relatively low, this is because students are not so interested in biology lessons, they quickly feel bored because the applied learning approach still does not provide motivation for students to more spirit in learning. Metacognitive skills also need to be mastered by the teacher so that students can have high metacognitive skills. Because metacognitive skills enable students to plan, keep track of, and monitor their learning. Type of research used is experiment. Population is the entire subject or a large group of research amounted to 47. Sample is partially or representative of the population under study using random sampling technique (randomly). From the final test result in the experimental class using bridging analogy learning approach, the grade averaged 79.57, while in the control class without using bridging analogy learning approach, the average grade was 70.00. After data analysis, obtained tcount = 2.65 and ttable = 1.68 turns thitung> ttabel. This means H0 is rejected and H1 accepted so it can be concluded that there is influence in the application of bridging analogy learning approach to improve students' metacognitive ability at 95% confidence level. Keywords: Learning Approach, Bridging Analogy, Metacognitive Ability.